In session extinction and outcome in Virtual Reality Exposure Therapy for PTSD. (October 2018) - Rauch, Sheila A.M.; Koola, Catherine; Post, Loren; Yasinski, Carly; Norrholm, Seth D.; Black, Kathryn; Rothbaum, Barbara O.
Abstract: Recent research emphasizes emotional engagement and between-session extinction, but no longer within-session extinction, as the primary mechanisms underlying exposure therapy for the treatment of PTSD. No previous studies have examined change in subjective units of distress (SUDS) in virtual reality exposure (VRE) for PTSD despite its potential facilitation of engagement (see McLay et al., 2012; Reger & Gahm, 2008). Using in session data from Rothbaum et al. (2014) we examined patterns of within- and between-session SUDS change in veterans receiving VRE for PTSD augmented byd -cycloserine, alprazolam, or placebo. The number of treatment sessions significantly predicted SUDS rating ( t = −7.74, p < 0.001). Time in session continued to serve as a significant predictor of SUDS ( t = 13.44, p < 0.001). Specifically, engagement increased within session and then reduction (extinction/habituation) was apparent across sessions. Treatment group was a predictor of SUDS rating within treatment sessions ( t = 2.26, p < 0.05) but not across sessions, such that participants receiving medication experienced greater increases in SUDS within-session than those receiving placebo. Responder status was a predictor of SUDS reduction across treatment sessions ( t = −4.43, p < 0.001) but did not produce an overall or within-session effect on SUDS. Thus, medications impact within-session SUDS changes but do not impact between-session reductions in SUDS- the change most consistently and closely related to magnitude of therapeutic change and responder status.